2011
DOI: 10.1007/s12250-011-3210-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends of drug-resistant HIV-1 among drug-treated patients in former blood donors in Hubei, China: a three-year surveillance from 2004 to 2006

Abstract: This study aimed to evaluate emerging trends of drug resistance to nucleoside reverse transcriptase inhibitors (NRTIs) and nonnucleoside reverse transcriptase inhibitors (NNRTIs) among 290 former blood donor HIV-1 infected patients in Hubei, China, from 2004 to 2006, all of whom had received anti-HIV-1 therapy. The presence of NRTI- and NNRTI-associated mutations were established by sequencing; genotypic and predicted phenotypic drug resistance were evaluated using HIVdb Program version 5.0.1 (http://hivdb.sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have reported that DDI-based regimens are associated with higher rates of emergence of liver disease, [13] virologic failure, [14] prevalence of HIVDR [15]–[17] and mortality. [18] It is possible that because DDI is associated with more side effects compared with 3TC-based regimens, patients are less likely to stay adherent to drug intake and clinical visits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that DDI-based regimens are associated with higher rates of emergence of liver disease, [13] virologic failure, [14] prevalence of HIVDR [15]–[17] and mortality. [18] It is possible that because DDI is associated with more side effects compared with 3TC-based regimens, patients are less likely to stay adherent to drug intake and clinical visits.…”
Section: Discussionmentioning
confidence: 99%
“…The reports showed that 34.2% of former paid blood donor individuals in the Henan province [17] had at least one drug-resistance mutation to one antiviral drug, 23.7% were cross-resistant to NRTIs and NNRTIs after a 12-month duration and the prevalence of drug resistance in the ART individuals in a cross-section survey from 2004 to 2006 in the Hubei province [18]. In the present study, the prevalence of drug resistance was lower (2.1%) in the therapy-naïve than the ART-failure individuals, which was consistent with the results reported in the domestic study [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Both activities are essential for HIV replication 3; 4 ; yet, all current RT-directed therapeutics target only RT DNA polymerase activity. The continued emergence of HIV variants resistant to these and all other clinically used drugs 5; 6; 7; 8; 9 underscores the need to develop drugs against new targets such as RNase H that may be effective against resistant viruses. Despite considerable effort, no clinically useful drugs targeting RT RNase H have been developed.…”
Section: Introductionmentioning
confidence: 99%